Sobre o uso da DFT-s-OFDN generalizada para reduzir a interferência inter-numerologia em redes 5G-NR - Czekailo, Gláucio Porcides (2022)
Orthogonal Frequency Division Multiplexing (OFDM) systems with a Cyclic Prefix (CP-OFDM) are the base waveform in fifth-generation New Radio (5G-NR) mobile networks, with the Discrete Fourier Transform precoded version (DFT-s-OFDM) as an alternative in Peak-to-Average Ratio (PAPR) limited scenarios. However, since 5G-NR networks use multiple numerologies, the coexistence of these numerologies introduces a novel non-orthogonality in the system, known as Inter-Numerology Interference (INI). The present work proposes an alternative to the use of the CP by means of the Generalized-Discrete Fourier Transform-spread-Orthogonal Frequency Division Multiplexing (G-DFT-s-OFDM) waveform. Our results show that the use of the G-DFTs-OFDM waveform significantly reduces the INI in 5G-NR networks.